ON THE MEAN CURVATURE OF MIXED TYPE SURFACES IN LORENTZ-MINKOWSKI SPACE - Karagoz, Serpil (IJRDO -JOURNAL OF MATHEMATICS, 2023)
In this paper, we study on mixed type surfaces in Lorentz-Minkowski space and give a theorem on the mean curvature of the surface with the degeneracy of first fundamental form.